Genetic dissection of leaf rust resistance in a diversity panel of tetraploid wheat (Triticum turgidum) - Jitendra Kumar Yadav; Shruti Sinha; Hariom Shukla; Ankur Singh; Tanmaya Kumar Sahu; Shailendra Kumar Jha; Jyoti Kumari; Manjusha Verma; Sundeep Kumar; Rakesh Singh; Gyanendra Pratap Singh; Amit Kumar Singh (BMC Plant Biology)
Abstract Background Leaf rust, caused by Puccinia triticina Eriks (Pt) is a major threat to wheat cultivation worldwide. The rapid evolution of this pathogen has led to the emergence of new virulent strains that can overcome the resistance of commonly cultivated wheat varieties. To address this threat, continuous monitoring of leaf rust pathotypes is conducted in wheat-growing regions across the world. This approach helps prioritize the development and deployment of resistant cultivars, as well as the implementation of other effective control measures against the prevailing races. The key wheat leaf rust pathotypes in India include 77–5 (121R63-1), 77–6 (121R55-1), 77–9 (121R60-1), 12–5 (29R45), and 104 (17R23). Among these pathotypes, 77–5 (121R63-1) and 77–9 (121R60-1) are the most prevalent since 2016. As virulent pathotypes continue to evolve and adapt, there is an urgent need to continually explore the vast germplasm repositories of wheat and its related species to identify novel genetic resources and genes that confer resistance to these evolving leaf rust pathotypes. Therefore, the present study aims to identify genes and genomic regions responsible for leaf rust resistance against prevalent pathotypes in India, focusing on a subset of the Global Durum Wheat Panel, which includes genotypes from various tetraploid wheat species. Results This study revealed wide variation in seedling-stage resistance among 189 tetraploid wheat accessions against five prevalent leaf rust pathotypes in India namely, 77–5 (121R63-1), 77–6 (121R55-1), 77–9 (121R60-1), 12–5 (29R45) and 104 (17R23). Approximately 45% of the population exhibited immune/highly resistant to moderately resistant responses to pathotypes 77–5, 77–6 and 104, while around 23–27% showed similar levels of resistance to pathotypes 77–9 and 12–5. A genome-wide association study using six multi-locus models identified 88 significantly associated quantitative trait nucleotides (QTNs) across the five leaf rust pathotypes. Among these, 22 QTNs were considered reliable, including four for pathotype 77–5, six for 12–5, three for 77–9, seven for 104, and two for 77–6. Among the 22 reliable QTNs, 10 coincided with the rust resistance regions reported in previous studies, whereas 12 appeared to be novel. Further investigations of the regions flanking all 88 QTNs revealed 300 genes, including 62 associated with disease resistance or defense responses. In silico expression analysis of these defense-related genes revealed two nucleotide-binding site–leucine-rich repeat genes: one on chromosome 6B (TRITD6Bv1G224600) near QTN RAC875_c35430_373, and another on chromosome 6A (TRITD6Av1G225060) in the vicinity of QTN Excalibur_c77841_224 with significantly higher levels of expression in the leaf-resistant genotype during the early hours of Pt infection. Therefore, these two genes could be potential candidates for resistance to leaf rust in tetraploid wheat germplasm. Conclusions Our study provides a comprehensive understanding of the genetic basis underlying leaf rust resistance in a diverse tetraploid wheat germplasm panel. It has also revealed novel candidate genomic regions for leaf rust resistance. These genomic regions represent important targets for inclusion in marker-assisted breeding initiatives, aimed at fostering durable resistance against leaf rust disease.